Peningkatan Kualitas Layanan Usaha Kesehatan Sekolah se-Kecamatan Segedong - Henry Maksum; Suriani Sari; Muhammad Suhairi; Nevi Hardika; Zusyah Porja Daryanto; Ashadi Cahyadi; Ade Rahmat (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Community service is non-formal education to the wider community, through educational activities, socialization, training, seminars and educational activities that can support community development. Education to the community is one of the implementations of the tri dharma of higher education. Community service through seminars on Improving the Quality of School Health Services in Segedong District is an effort to maintain a healthier life. The category of clean and healthy living in the school environment is a set of behaviors that are practiced by students, teachers and the school community on the basis of awareness as a result of learning, so that they are independently able to prevent disease, improve health, and play an active role in creating a healthy school environment. This Community Service aims to provide education to children, teachers, school health business managers in each school about healthy and clean living behavior in order to create a healthy nation generation. The result of this community service is an increase in knowledge about school health business management skills in healthy and clean living behavior in schools.